Mating suppresses sperm-dependent male avoidance in C. elegans hermaphrodites - Satoshi Suo (PLoS ONE, 2026)
In many sexually reproducing animals, females incur higher reproductive costs and therefore tend to be more selective in accepting mates. In Caenorhabditis elegans , self-fertilizing hermaphrodites produce a limited number of self-sperm, and previous studies have suggested that hermaphrodites avoid males. However, the behavioral dynamics of this male-avoidance behavior remain largely unexplored and its underlying mechanisms are not well-understood. Here, I quantitatively analyzed male-avoidance behavior in C. elegans hermaphrodites by measuring locomotor speed in the presence of males. Automated image analysis revealed that wildtype hermaphrodites increased speed when in contact with males, indicating active avoidance behavior. In contrast, avoidance was significantly reduced in sperm-deficient mutant hermaphrodites and aged hermaphrodites that had exhausted self-sperm. Similarly, females of gonochoristic Caenorhabditis species, which lack self-sperm, also showed no avoidance of males. These results suggest that the presence of self-sperm promotes male avoidance, likely to favor self-fertilization. Interestingly, hermaphrodites that had previously mated with males showed reduced male avoidance. Given that male-derived sperm outcompete self-sperm for fertilization, continued avoidance after mating may be no longer advantageous for reproduction. These findings highlight the adaptive nature of sperm-dependent male avoidance in C. elegans hermaphrodites.